The impact of using distance education technology in developing the academic achievement of mathematics for eighth- grade learners in light of the Corona crisis – Field study on the secondary eighth graders in Damascus city – - Drwish, Drwish Hasan; Engin, Ali Osman (Journal of Curriculum and Teaching Methodology, 2022)
The current study aimed to reveal the impact of the use of distance learning technology in developing the academic achievement of secondary stage learners in light of the Corona crisis in public schools. As well as to identify the significance of the differences in the impact of the use of distance education technology in developing the academic achievement of secondary stage learners in light of the Corona crisis. The study was applied in the first semester of (2021), and the descriptive survey method was used. The study community consisted of secondary school students in public schools of Damascus Education. The study consisted of (167) male and female students. The number of male sample members (89), and the number of females (78) were chosen by simple random method. The study concluded the following results:The arithmetic averages ranged between (3.40- 4.72), where came in paragraph (1) which states “distance learning enriches my education” comes in the first place, with an arithmetic average of (4.72). While paragraph (19) which its text "helped to eliminate many student problems" came in the last rank, with an average of (3.40). While the results of the main question about the effect of using distance education technology in developing the academic achievement of secondary stage learners in Damascus Education schools in light of the Corona crisis showed that there is a positive impact of using distance education in light of the Corona crisis. That positive impact was in a medium degree. Where the average arithmetic of perceptions of the sample members (4.03), and standard deviation (0.42), and a medium degree for the field as a whole. In light of the results, the researcher made the following recommendations: Conduct more studies and research on different samples and stages. Provide adequate support to the Ministry of Education in order to maintain its continuity and its ability to manage distance education. Support national projects that develop the idea of ​​distance education, and enhance cooperation with the Syrian Ministry of Education.
Keywords: distance education; secondary graders; Corona crisis; academic achievement